The Potential Mechanism Behind Native and Therapeutic Collaterals in Moyamoya - Bao, Xiang-Yang; Fan, Yan-Na; Wang, Qian-Nan; Wang, Xiao-Peng; Yang, Ri-Miao; Zou, Zheng-Xing; Zhang, Qian; Li, De-Sheng; Duan, Lian; Yu, Xin-Guang (Frontiers in Neurology, 2022)
Background and Purpose To explore the genetic basis and molecular mechanism of native arteriogenesis and therapeutic synangiosis in moyamoya disease (MMD). Methods An angiography-based study using patients from a prospective trial of encephaloduroarteriosynangiosis (EDAS) surgery was performed. The spontaneous collaterals grades were evaluated according to the system described by a new grading system. Blood samples were collected from all the recruited patients before EDAS and during the second hospitalization 3 months post-EDAS. We performed Boolean analysis using a combination of specific cell surface markers of CD34briCD133+CD45dimKDR+. Genotyping of p.R4810K was also performed. The correlation of age, sex, initial symptoms at diagnosis, collateral grade, Suzuki stages, the RNF213 genotype, time to peak (TTP), and endothelial progenitor cell (EPC) count with good collateral circulation was evaluated. Results Eighty-five patients with MMD were included in this study. The mutation rate of RNF213 p.R4810K in our study was 25.9% (22/85). The heterozygous mutations were occurred significantly more frequently in the cases that were presented with infarction, worse neurological status, severe posterior cerebral artery (PCA) stenosis, and longer TTP delay. Further, the heterozygous mutations occurred significantly more frequently in the poor collateral stage group. Lower grades were significantly correlated with severe ischemia symptoms, worse neurological status, and a longer TTP delay. The post-operative angiographic findings showed that a good Matsushima grade was correlated with heterozygous mutations, a lower collateral stage, and a longer TTP delay. The CD34briCD133+CD45dimKDR+ cell count in patients 3 months post-EDAS was significantly higher as compared to the count before EDAS in the good Matsushima grade group. However, this change was not observed in the poor Matsushima grade group. Conclusions These data imply that mutations of RNF213 p.R4810K affect the establishment of spontaneous collateral circulation, and EPCs are involved in the process of formation of new EDAS collaterals.